COMMUNITY-BASED CULTURAL TOURISM AND LOCAL TOURISM IN THE GLOBALIZATION CENTER - Darmana, K. (Jurnal IPTA (Industri Perjalanan Wisata), 2019)
Cultural tourism is an important issue in the global tourism industry, in a global context claimed to distort customs and traditions as local wisdom. The main problem to be answered is (1) What is the form of community-based Using cultural tourism ?, (2) How is the management of the global tourism market management? (3) What is the development strategy in global competition? The purpose of this study is to understand the forms of Using culture tourism, its management techniques, and its development strategies. Qualitative methods to answer the problems and objectives of this study involving a number of informants. Data collection is based on in-depth interview techniques, participatory observation, and document study. Qualitative data analysis through the stages of reduction, categories and classifications, determining themes, and drawing conclusions. The framework of cultural tourism theory in ecotourism, community-based cultural tourism, and management of cultural tourism management support analysis and writing. The results of this study are 2 forms of Using cultural tourism: tangible and intangible tours. Tangible tourist attraction objects are: Using home architecture, Using tourist parks, rice fields, Balai Paseban Buyut Chili , and culinary. Intangible attractions such as Using customs, life cycle ceremonies, and Using art. All forms of tourism are managed by the synergy of three components of Using tourism, namely: Using traditional institutions, Using tourism conscious groups (pokdarwis), and private parties. Using traditional institutions of representation of citizens of the Using community, Pokdarwis representation from the government, and private representation from investors. The form of development strategies such as the accessibility and amenities of tourism by the government, customs, traditions, and Using arts are synergies between local communities and government, marketing and human resources synergy tourism between local, government and private communities. Community and government participation is more dominant in its development. Internet support, and social media networks appear to play a lot in development, especially marketing, promotion, storytelling and service. The issue of conservation, preservation, and sustainability of Using tourism resources, has not been considered development because the economic aspects are the targets and objectives. In the future, the mainstreaming of this aspect is prioritized so that community-based Using cultural tourism and local wisdom can be dynamic in the global era.